PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE : Studi Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia - Mikha Btari Batubara (2021)
This study aims to find out the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) towards Tax Avoidance. Good Corporate Governance is proxy by institutional ownership, independent commissioner, and audit committee, while Corporate Social Responsibility (CSR) is proxy by Corporate Social Responsibility Disclosure Index (CSRDI) and Tax Avoidance is proxied by Current Effective Tax Rate (CuETR). The object of this research is mining companies that listed in Indonesia Stock Exchange (IDX) for the 2017-2019 period, with a total sample of 22 companies or 66 observation data selected by purposive sampling method. The data are secondary data that obtained from companies website or Indonesia Stock Exchange (IDX) website and the data analysis by multiple regression analysis. The results show that institutional ownership, audit committee, and Corporate Social Responsibility have no significant effect on Tax Avoidance meanwhile independent commissioner have a negative significant towards Tax Avoidance.